Divine subjectivity and intersubjectivity - Zagzebski, Linda Trinkaus (Religious studies, 2024)
This article expands my previous work on omnisubjectivity, the divine property of having a complete and perfect grasp of the subjective states of all beings who have such states. By a subjective state I mean a conscious state as that state is experienced by the one who has it. I argue that only a being with subjectivity can be omnisubjective, and therefore, God has subjective states. The article explores the subjectivity of God as it applies to the Christian doctrines of the Trinity and the Incarnation, focusing on the important difference between a person and an instance of a nature. I propose that the uniqueness of persons is grounded in their unique subjective states, not their objective nature. Each person of the Trinity has a unique point of view and unique subjectivity even though they share an objective divine nature instantiated in a single divine being. The Son has a single set of subjective states before, during, and after the Incarnation. Each member of the Trinity is omnisubjective and fully grasps the unique subjective states of each other person of the Trinity. The perfect comprehension of each other while remaining unique persons is a model of perfect love within a community of persons.